Enriching Research in Academic Institutions - Kalanidhi, A. (Journal of Engineering Education Transformations, 2011)
The role of research in academic institutions has been emphasized. A new model has been proposed for absorption into the academic world. Au-Kalanidhi models proposed here has been tested in three universities and hence the robustness of the model works out to be a time tested model. As research plays important role in the quality of institution. it is proposed for setting up an Accreditation council to evaluate standards of research institutions across the globe. Preparatory work on the International Accreditation Council of Research has also been enumerated.